Diversity and Abundance of Landsnails in Kwararafa University, City Campus, Wukari, Taraba State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The diversity and abundance of terrestrial snail species within the Kwararafa University community was carried out in this study, highlighting their ecological significance and potential threats to their populations. A total of 740 snails were collected, with Achatina achatina being the most abundant species. Comparative analysis with previous studies revealed variations in species composition and abundance, possibly influenced by habitat differences. Soil nutrient analysis indicated correlations between snail abundance and calcium levels, suggesting the importance of soil composition in snail ecology. Low diversity and uneven distribution patterns were observed which were potentially attributed to human disturbances like urbanization. Recommendations include raising awareness about the ecological importance of snails, mitigating threats to their populations, and conservation efforts to prevent species from been endangered. Thapsia sp, a collected species, was identified as endangered, emphasizing the urgency for conservation actions. This study underscores the need for further research to document and conserve snail fauna across Taraba State communities.